A visual semiotic analysis of multicultural values in an Indonesian English textbook - Isnaini, Filza; Setyono, Budi; Ariyanto, Sugeng (Universitas Pendidikan Indonesia, 2019)
In the context of the role of culture in language learning, many textbook analysts have so far investigated the representations of cultures in EFL textbooks. Most of the previous findings on the study of culture indicate that EFL textbooks contain more about the cultures of inner circle countries compared to the expanding and outer circle countries. In Indonesia, this area of cultural issues in English textbooks appears to be underexplored. To narrow the gap, this study using the visual semiotic theory of Barthes (1977) examined the multicultural values represented in an Indonesian vocational high school English textbook through the visual images in the textbook. This study shows that there are four categories of multicultural values represented in the EFL textbook: respecting other people’s tradition, appreciating other people’s perspectives, appreciating other people’s cultural products, and appreciating women’s equal rights. These insights give students opportunities to enhance their intercultural communication competence (ICC) by appreciating cultural diversity and accepting racial and religious differences around them.